Transidentität im System der Grund- und Menschenrechte Eine kritische Analyse der deutschen und europäischen (Rechtsprechungs-)Entwicklung - Neßmann, Florina (Universitätsverlag Göttingen, 2022)
The dissertation analyzes the German and European legal situation and the development of case law on the subject of transgender identity in the system of fundamental and human rights. The work focuses primarily on the case law of the Federal Constitutional Court and the European Court of Human Rights, but also takes a comparative legal approach and deals with the Charter of Fundamental Rights of the European Union. Both the Federal Constitutional Court and the European Court of Human Rights provided important stimulus for legal reforms. The major legal issues examined in the work include the prerequisites for the change of legal gender, the change of first name, the legal consequences of a gender change for the continued existence of a marriage and the recognition of transsexual men and women as fathers or mothers, as well as the legal requirements for the assumption of costs for gender reassignment surgeries.